2022
DOI: 10.1088/1361-6463/ac9ac3
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable enhancement in catechol sensing by the decoration of selective transition metals in biphenylene sheet: A systematic first-principles study

Abstract: Motivated by the recent successful synthesis of biphenylene structure [Science 372, (2021), 852], we have explored the sensing properties of this material towards the catechol biomolecule by performing the first-principles density functional theory and molecular dynamics simulations. Pristine biphenylene sheet adsorbs catechol molecule with a binding energy of -0.35 eV, which can be systematically improved by decorating the transition metals (Ag, Au, Pd, and Ti) at various possible sites of biphenylene. It is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Unlike the primitive hexagonal structure of graphene with a C-C bond length of 1.426 Å, 36 the biphenylene monolayer is composed of C 4 , C 6 and C 8 rings and shows different C-C bond lengths ranging from 1.408 Å to 1.461 Å, well matching the reported results. 34…”
Section: Model Of the Biphenylene Monolayermentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the primitive hexagonal structure of graphene with a C-C bond length of 1.426 Å, 36 the biphenylene monolayer is composed of C 4 , C 6 and C 8 rings and shows different C-C bond lengths ranging from 1.408 Å to 1.461 Å, well matching the reported results. 34…”
Section: Model Of the Biphenylene Monolayermentioning
confidence: 99%
“…Beyond graphene dominated by the periodic hexagonal rings, several carbon allotropes composed of hybrid carbon rings have been recently predicted by first-principles calculations or synthesized experimentally. [22][23][24][25][26][27][28] Biphenylene, as a novel 2D carbon material consisting of four-(C 4 ), six-(C 6 ) and eight-membered (C 8 ) carbon rings, shows great potential in applications such as catalysis, 29,30 batteries, 31 sensors, [32][33][34] etc. The hybrid carbon rings at the biphenylene monolayer surface introduce non-equivalent carbon sites and improve the interfacial activity, such that the biphenylene monolayer can be easily oxidized and shows more active carbon sites for chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the previous study shows small Cc adsorption energy on the pristine TM dichalcogenides (TMDCs) like MoS 2 and VSe 2 . , The TM functionalization has increased the conductivity and helped to increase the interaction of Cc. Graphene-like carbon 2D materials like gamma graphyne, hole graphyne (hGY), and biphenylene (Bp) were also predicted to be excellent Cc sensors. The significant adsorption energy for Cc on the hGY system was due to the charge transfer between the 2p orbitals of Cc and the 3d orbitals of the decorated Sc atom on the hGY system. In the Bp system, though Ti decorations show higher sensitivity toward the Cc molecule than the Pd decorated system, the Pd + Bp system is the best due to the short recovery at 500 K.…”
Section: Introductionmentioning
confidence: 99%
“…[33] investigated the TM (Ag, Au, Pd) decorated 2D VSe 2 as an effective and reversible CCdetecting material. Mahamiya et al [34] have reported the excellent sensing behavior of recently synthesized biphenylene sheet decorated with TMs towards CC biomolecule.…”
Section: Introductionmentioning
confidence: 99%